The Esophago-gastric cervical anastomosis. Does it protect from mediastinitis? - Piñeyro, Alberto; Bergalli, Luis; Piacenza, Guillermo; Rodríguez, José L; Misa, Carlos (Cirugía del Uruguay, 1987)
4 cases of clínico-radiological contamination of pleura and mediastinum alter cervical esophago-gastric anastomosis in surgery of esophageal cancer are presentad. To avoid this compllcatlon of the cervical suture, essential technical details are established.